DOUBLE-BURDENED AND MARGINALIZED WOMEN: Patriarchal Dominance in the Development in Padang Lawas, North Sumatera - Pohan, Muslim (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2022)
Village Law Number 6 of 2014 stipulates the principles of participation, equality, and empowerment to make women subordinate in village development. This discourse cannot be separated from the role of the Batak Angkola Padang Lawas community, which is deeply committed to the patriarchal system. Women who work in development must face this well-established wall of old social construction. The study intends to investigate the reasons why women are marginalized in this development agenda. The data was gathered through documentation and interviews. Based on the patriarchal theory of Walby, it is safe to say that the construction of women's positions in village development in Padang Lawas is a manifestation of constructed patriarchal culture, which has long been part of Batak culture. Women's "lower education" than men's places them in an unfavorable position. The patriarchal dominance in the clan structure and dual roles as housewives perpetuate and gloss over this poignancy on a daily basis.[Undang-Undang Desa Nomor 6 Tahun 2014 mengatur prinsip partisipasi, kesetaraan, dan pemberdayaan untuk menjadikan perempuan tersubordinasi dalam pembangunan desa. Wacana ini tidak lepas dari peran masyarakat Batak Angkola Padang Lawas yang sangat kental dengan sistem patriarki. Perempuan yang bekerja dalam pembangunan harus menghadapi tembok konstruksi sosial lama yang sudah mapan ini. Studi ini bermaksud untuk menyelidiki alasan mengapa perempuan terpinggirkan dalam agenda pembangunan dalam kontek Desa Padang Lawas. Pengumpulan data dilakukan melalui dokumentasi dan wawancara. Berdasarkan teori patriarki ala Walby, dapat dikatakan bahwa posisi perempuan dalam pembangunan desa di Padang Lawas merupakan wujud dari konstruksi budaya patriarki yang telah lama menjadi bagian dari budaya Batak. "Pendidikan perempuan yang lebih rendah" daripada laki-laki menempatkan mereka pada posisi yang tidak menguntungkan. Dominasi patriarki dalam struktur klan dan peran ganda sebagai ibu rumah tangga mengabadikan dan memoles kepedihan ini setiap hari.]